Apply Anticoagulants after Discharge not Benefit to the Incidence of Symptomatic Thrombus in High‐Altitude Areas: A Retrospective Study - Xiangji Dang; Zhilong Liu; Xiaoyun Sheng; Yan Liu (Orthopaedic Surgery, 2023)
Objective Many guidelines indicate that continuous use of anticoagulant drugs reduces the incidence of venous thrombus (VT), but no studies show the effect on the incidence of symptomatic venous thrombus (SVT) in total knee arthroplasty (TKA) patients after discharge. This study aimed to investigate whether it is necessary to apply anticoagulants to TKA patients after discharge. Methods Patients who met the exclusion criteria requirement, underwent TKA by the same surgical team and received anticoagulant therapy after the operation were eligible for the study. Finally, a total of 567 TKA patients were recruited as participants. The patients were divided into two groups. The patients in group A were taken low molecular heparin for 5–10 days after surgery, which included but was not limited to low molecular weight heparin calcium injection (0.4 mL, ih, Qd), calcium dioxin injection (0.6 mL, ih, Qd), or enoxaparin sodium injection (0.4 mL, ih, Qd), and the patients needed to continue oral anticoagulant drug (10 mg, po, Qd) for 7–21 days after discharge. The patients in group B only took low molecular heparin 5–10 days after surgery and no treatment after discharge. The baseline characteristics of patients, total complications of SVT include lower limb vascular pain (LLVP), lower limb vascular pain no fester (LLVPNF), lower limbs swelling (LLS), lower limb fester (LLF), and death by thrombosis (DT), bleeding and mortality following discharged were compared between two groups. Results The study showed that the incidence of SVT patients had no significant difference between the two groups (p = 0.489). Moreover, the incidence of LLVP (p = 0.265), LLS (p = 0.84), LLVPNF (p = 0.213), LLF (p = 0.907), DT (p = 0.907), death from other causes, and bleeding (p = 0.323) had no significant differences between the two groups. However, the incidence of SVT in patients with smoking (p = 0.0001 or 0.0011) or drinking (p = 0.0002 or 0.0001) was significantly increased. Conclusion There is not enough evidence showing that the TKA patients given anticoagulants after discharge had benefits in decreasing the risk of SVT. Furthermore, smoking and drinking would significantly increase the risk of SVT in TKA patients.